2018
DOI: 10.3389/fphys.2018.00896
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Inter-individual Variability in the Therapeutic Response of Blood Glucose Control to Exercise in Type 2 Diabetes: Going Beyond Exercise Dose

Abstract: In the context of type 2 diabetes, inter-individual variability in the therapeutic response of blood glucose control to exercise exists to the extent that some individuals, occasionally referred to as “non-responders,” may not experience therapeutic benefit to their blood glucose control. This narrative review examines the evidence and, more importantly, identifies the sources of such inter-individual variability. In doing so, this review highlights that no randomized controlled trial of exercise has yet prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 116 publications
3
49
0
Order By: Relevance
“…Similar results were found for medium‐term interventions (8–16 weeks), with small to large improvements in HbA1c and in oral glucose tolerance test‐derived variables, including fasting blood glucose and HOMA‐IR . The differences between these results and our own might be explained by several sources of inter‐individual variability, including exercise dose, exercise frequency, exercise type, behavioral/environmental barriers, exercise‐meal timing, or the effect of anti‐hyperglycaemic drugs on changes in blood glucose control . For instance, although substantial changes in pharmacological therapy (ie, changing from oral medication to insulin therapy) constituted removal from PPA, more subtle changes in oral medication were not controlled, which may have blunted the effects of the exercise groups on glycaemic control.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were found for medium‐term interventions (8–16 weeks), with small to large improvements in HbA1c and in oral glucose tolerance test‐derived variables, including fasting blood glucose and HOMA‐IR . The differences between these results and our own might be explained by several sources of inter‐individual variability, including exercise dose, exercise frequency, exercise type, behavioral/environmental barriers, exercise‐meal timing, or the effect of anti‐hyperglycaemic drugs on changes in blood glucose control . For instance, although substantial changes in pharmacological therapy (ie, changing from oral medication to insulin therapy) constituted removal from PPA, more subtle changes in oral medication were not controlled, which may have blunted the effects of the exercise groups on glycaemic control.…”
Section: Discussionsupporting
confidence: 80%
“…10,13,14,16,27,28 The differences between these results and our own might be explained by several sources of inter-individual variability, including exercise dose, exercise frequency, exercise type, behavioral/ environmental barriers, exercise-meal timing, or the effect of antihyperglycaemic drugs on changes in blood glucose control. 29 For instance, although substantial changes in pharmacological therapy (ie, changing from oral medication to insulin therapy) constituted removal from PPA, more subtle changes in oral medication were not controlled, which may have blunted the effects of the exercise groups on glycaemic control. On the other hand, the first month and a half was used as a period of adaptation in the HIIT group, in order to prepare patients for the HIIT protocol (1:1 bouts at 90% HRR).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the exercise-induced weight change, the large amount of variation seen in the response, ranging from weight gain to weight loss, is consistent with what has been observed in mice as well as humans (Hiramatsu & Garland, 2018;Kelly et al, 2014;King et al, 2017;Pickering & Kiely, 2019;Solomon, 2018;Stephens & Sparks, 2015;Vellers et al, 2018). The fact that female flies show a clear correlation between the amount of exercise performed and the exercise-induced weight change is a promising result, that will require further study.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have observed that several individuals reduced their resting energy expenditure, increased energy intake, lowered physical activity levels or reduced fat oxidation rate in response to the exercise‐associated increase of energy expenditure or energy intake restriction programs . On the other hand, although differences in the adherence to the intervention programs could also explain interindividual variability in the responsiveness, it has not been previously studied . As far as we are aware, there are no previous studies comparing the prevalence of responders between two different lifestyle programs differentiated by the inclusion or not of exercise.…”
Section: Discussionmentioning
confidence: 92%